The investigation of nitrogen, phosphorus, and potassium fertilizer on the productivity of various Sorghum bicolor varieties - EKA HANDAYANTA; FAROUQ HEIDAR BARIDO; SAMANHUDI SAMANHUDI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Handayanta E, Barido FH, Samanhudi. 2024. The investigation of nitrogen, phosphorus, and potassium fertilizer on the productivity of various Sorghum bicolor varieties. Biodiversitas 25: 2763-2768. Sorghum (Sorghum bicolor L. Moench) is a unique cereal crop characterized by its regenerative capacity post-harvest, with varieties including Super, Suri, Numbu, and Keller. This investigation sought to elucidate the impact of varying fertilizer levels on the forage productivity of these sorghum varieties. The experiment employed was a Completely Randomized Design (CRD) with a 4×5 factorial arrangement and three replications. The first factor comprised the sorghum varieties (V1 = Super, V2 = Suri, V3 = Numbu, V4 = Keller), while the second factor pertained to the levels of NPK fertilizer (P0 = 0 kg/ha, P1 = 173 kg/ha, P2 = 346 kg/ha, P3 = 519 kg/ha, P4 = 692 kg/ha). Data were subjected to Analysis of Variance (ANOVA), and significant differences were further analyzed using the Duncan Multiple Range Test (DMRT). The study concluded that while there was no interaction between the sorghum variety and NPK fertilization levels, the sorghum variety significantly influenced (P<0.05) protein and crude fat production but not dry matter and crude fiber production (P>0.05). The NPK fertilization levels significantly affected (P<0.05) the production of dry matter, protein, fat, and crude fiber. The study deduced that a 692 kg/ha fertilization dose yielded the highest dry matter, protein content, crude fat, and crude fiber production.